Analisis Penggunaan E-Commerce Shopee Melalui Niat Penggunaan Berkelanjutan dengan Expectation Confirmation Model - Jonathan Devrinno; Dewi Sinta Febriani; Ayundha Wardhatul Fitrah (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this study is to conduct an in-depth analysis of the use of the Shopee e-commerce platform through the perspective of sustainable use intention by applying the Expectation Confirmation Model. This study aims to identify the factors that influence users' continued intention to use Shopee and their behavior after use. In a context of increasing need for sustainability, understanding how e-commerce can be used in a sustainable manner becomes very important. This study uses a quantitative approach with classification. The data obtained is primary data obtained through distributing questionnaires to 50 respondents. This study also uses the Structural Equation Modeling (SEM) technique with the Partial Least Square (PLS) method approach. The results of this study state that the intention to continue using Shopee E-commerce services increases by considering several factors, namely confirmation, perceived security, and self-efficacy. Meanwhile, perceived usefulness and satisfaction factors have no effect on the intention to use the service continuously.